OUTBREAK OF RESPIRATORY SYNDROME IN CHUKAR PARTRIDGE (ALECTORIS CHUKAR) - M. Lateef; U. Rauf; M.A. Sajid (Journal of Animal and Plant Sciences, 2006)
On a visit to a farm, most of the birds (chukar partridge) in releasing pens were with symptoms of dullness, depression and emaciation. On postmortem examination severe enteritis, carcass emaciation and pus in the ocular and nasal sinuses was observed. Bacterial cultures obtained from the pus have cocci, coccobacilli and rods like morphological characters suspecting of salmonellae, streptococci, staphylococci, bacilli and mycoplasmae species. Before proper diagnosis, birds were given tentative medication followed by the treatment based on laboratory investigations. Certain managemental programmes were also advised to the farmer as preventive measures.
Keywords: Respiratory syndrome; Chukar patridge; depression; emaciation